2021
DOI: 10.1002/eji.202049120
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 promotes CXCL12‐dependent egress of murine B cells from Peyer's patches in homeostasis

Abstract: High mobility group box‐1 protein (HMGB1) is an alarmin that, once released, promotes inflammatory responses, alone and as a complex with the chemokine CXCL12. Here, we report that the HMGB1–CXCL12 complex plays an essential role also in homeostasis by controlling the migration of B lymphocytes. We show that extracellular HMGB1 is critical for the CXCL12‐dependent egress of B cells from the Peyer's patches (PP). This promigratory function of the complex was restricted to the PPs, since HMGB1 was not required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…CXC chemokines are also classified as inflammatory, homeostatic, or dual function. CXCL12 is a homeostatic chemokine that can exist in monomeric and dimeric forms [18]; it has key roles in embryogenesis, angiogenesis, lymphopoiesis and regulates hematopoietic stem cell trafficking in physiological and pathological conditions [12,19,20].…”
Section: Cxcl12 and Its Receptors Cxcr4 And Cxcr7/ackr3mentioning
confidence: 99%
“…CXC chemokines are also classified as inflammatory, homeostatic, or dual function. CXCL12 is a homeostatic chemokine that can exist in monomeric and dimeric forms [18]; it has key roles in embryogenesis, angiogenesis, lymphopoiesis and regulates hematopoietic stem cell trafficking in physiological and pathological conditions [12,19,20].…”
Section: Cxcl12 and Its Receptors Cxcr4 And Cxcr7/ackr3mentioning
confidence: 99%
“…This may hinder the transmission of calcium ions within B cells, impacting the regulation of B-cell activation and differentiation (reviewed by 70 , 71 ). Additionally, the downregulation of Hmgb1-rs17 may contribute to the accumulation of splenic PCs and MBCs ( Figures 3 , 4 ) by inhibiting B-cell egress from lymphoid tissues, such as Peyer’s patches ( 72 ). The regulation of vaccine-derived responses by regulatory T cells (Tregs) could also be affected, as indicated by the downregulation of Gm10408 and Gm14391 ( Supplementary Table 1 ), potentially limiting their frequency or functionality in the spleens of Poly I:C-adjuvanted vaccinees ( Supplementary Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 has been demonstrated to affect B cells activation in response to endogenous TLR9 ligands [ 103 ] and through TLR2 and CD36 in inflammatory bowel disease [ 104 ]. Moreover, a recent study has demonstrated that the HMGB1–CXCL12 complex influences B-cell trafficking in Peyer’s patches (PPs) and IgA production in the intestine [ 105 ], and, even if this role was observed in homeostatic condition, it is possible that HMGB1 may exert similar effects during acute or chronic inflammation. All these data may suggest a possible role of HMGB1 in the regulation of B cells during the inflammatory reparative response that has not been investigated yet.…”
Section: Role Of Hmgb1 In the Inflammatory And In The Reparative Phases Following MImentioning
confidence: 99%